Corn yield in sandy soil fertilized with poultry litter - Barros, Juliana da Silva [UNESP]; Medeiros, Joao Carlos; Dalla Rosa, Jaqueline; Jesus Lacerda, Julian Junio de; Sousa, Daiane Conceicao de; Heberle Mafra, Maria Sueli (United Arab Emirates Univ, 2017)
The use of animal waste is an alternative to provide nutrients and increase organic matter content in sandy soils. The poultry litter is one of the most nutrient-rich residues. The objective of this study was assess the effect of poultry litter as organic fertilizer on productivity of corn and chemical properties of a sandy soil. The experiment was conducted at the experimental farm of the Federal University of Piaui, in the municipality of Bom Jesus, PI, Brazil. The treatments were poultry litter levels: 0 (control), 2, 4, 8, 12, 16 and 24 t ha(-1). We evaluated the effect of poultry litter on the soil chemical properties, plant growth and productivity of corn. We also evaluated the correlation between variables of the plant and soil chemical properties. The maximum productivity was obtained with the highest level poultry litter (24 t ha(-1)). Calcium, magnesium, phosphorus, potassium, pH, and soil organic matter increased due to the increase of poultry litter levels. The soil chemical properties have positive relationship with stem diameter and productivity of corn. The poultry litter is an organic fertilizer with potential of increase the productivity of the corn and meliorate the fertility of sandy soils.
Keywords: Organic fertilizer; Animal waste; Soil fertility